Attachment and its association to externalizing and internalizing behaviours amongst school-aged children in Mankweng, Polokwane - Ramoloto, Nthabiseng Phillipine (My University, 2013)
Refer to document
Thesis (M. A.( Clinical psychology)) -- University of Limpopo, 2013
Keywords: School children behaviours; Internalizing behaviours; Externalizing behaviours; School children -- South Africa.; Behaviorism (Psychology) -- South Africa; Attachment behavior in children -- South Africa